Analysis of Beginning Reading Difficulties of Dyslexic Students - Debi Tripuanti; Fitri Siti Sundari; Resyi A. Gani (Journal of International Multidisciplinary Research, 2024)
Reading skills are not something that can develop naturally like language development. However, in the development of reading which starts from the beginning of the development of this skill, it is necessary to carry out a systematic planning process, unlike language development. The systematic development in question is a planned development like a lesson. The purpose of this study was to analyze the factors that cause dyslexia students' early reading difficulties and efforts to overcome them. This research method uses a qualitative research method with a case study approach. Difficulty reading at the beginning of dyslexic students is the factor of students who have limitations and experience slow learning which can be called dyslexia, namely a person's ability to recognize letters with evidence from the results of psychological tests. reading difficulties caused by a person's ability to recognize letters.